Comprehensive Evaluation of Treatment Plans in Stereotactic Body Radiation Therapy (SBRT) for Lung Cancer Patients - Yanik, Ramiser; Dirican, Bahar (International Journal of Computational and Experimental Science and Engineering, 2025)
Non-Small Cell Lung Cancer (NSCLC) is a major public health problem and a leading cause of cancer-related deaths. Stereotactic Body Radiotherapy (SBRT) has emerged as a highly precise treatment modality that provides high biologically effective doses (BED) with superior dose compliance, high conformity and sharp dose falloff, and has an important place in the treatment of NSCLC. This study aims to evaluate the SBRT plans for 22 NSCLC patients by assessing the Conformity Index (CI), Heterogeneity Index (HI) and organs at risk (OAR) doses. Findings demonstrate that SBRT is effective in achieving tumor control in hypoxic and radio resistant tumor regions through precise target coverage and effective intra tumor dose heterogeneity. These features make SBRT a noninvasive and highly effective alternative to surgery for patients with early-stage NSCLC. This study highlights the unique effect of SBRT, a radiotherapy option that reduces doses to organs at risk while improving treatment outcomes, in the treatment of NSCLC and highlights its unique potential in the treatment of NSCLC by evaluating its dosimetric parameters.